Peran Tokoh Agama dalam Memperkuat Moderasi Beragama di RT 49 Desa Masangan Kulon Kecamatan Sukodono Kabupaten Sidoarjo - Jihan Aulia Salma; I Wayan Arsana (MISTER: Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This research is based on community life regarding the Role of Religious Leaders in Strengthening Religious Moderation in RT 49, Masangan Kulon Village, Sukodono District, Sidoarjo Regency. The objectives of this study are to 1) To determine the role of religious leaders in building religious moderation in RT 49 Masangan Kulon Village, Sukodono District, Sidoarjo Regency. 2) To find out what challenges religious leaders have in building religious moderation in RT 49, Masangan Kulon Village, Sukodono District, Sidoarjo Regency. This research involves interview, observation, and documentation techniques. In the framework of this study, it was found that people have understood the concept of religious moderation well, which is reflected in mutual respect between them. In the context of religious moderation, the role of religious figures continues to apply communicative and da'wah approaches to guide people towards goodness. The challenges faced by religious leaders in embracing diversity without compromising the essence of their teachings involve navigating the complexity of diverse values and beliefs within society.